When upper respiratory tract infections go rogue: A case report of Arcanobacterium haemolyticum Cerebral Abscess. (2021) - Adams, Nehkonti; Snitchler, Christopher; Kong, Michael; Ikeda, Daniel; Skinner, Anthony; Rodriguezbarrantes, Juan; Leverette, Ryan; Bell, Randy
Abstract: Arcanobacterium haemolyticum is an extremely rare cause of cerebral abscess. We present a unique case of Arcanobacterium haemolyticum sinusitis complicated by preseptal cellulitis and cerebral abscess. The patient initially presented with pharyngitis and then developed sinus congestion, headache and facial pain. Computed tomography and magnetic resonance imaging revealed a right gyrus rectus cerebral abscess and paranasal sinus infection. The patient underwent endoscopic sinus surgery and cultures revealed Arcanobacterium haemolyticum . Repeat imaging revealed maturation and progression of intracranial abscess. The abscess was drained and patient was treated with parenteral and oral antibiotics until complete clinical and radiological remission. This case highlights the importance of recognizing Arcanobacterium haemolyticum as a cause of invasive disease in immunocompetent hosts.